Mengelola Strategi Global: Menuju Terciptanya Keunggulan Bersaing Perusahaan dalam Bisnis Internasional - Hasa Nurrohim Kp (Sinergi: Kajian Bisnis dan Manajemen, 2006)
The terms of global strategy, global industry and global competition have been used widely in the last 20 years. Today, the issue has changed, especially to discuss (1) strategic alliance and its role in the global competition, (2) typology of global strategies, (3) matrix structure implementation of organization that implement complex global strategies. Asian countries play important role in the world economic now. Asian economic growth and poverty increase significantly, sowed by theory and research. Key issue of Asian management change is the development of business partnership among Asian countries or between Asia and developed countries like European and America. Partnership creates large opportunity to do global cooperation. Globalization run faster supported by internet. Everyone can access product and service he needed by internet.Keywords: global strategy, multidimensional, matrix structure, partnership, joint venture, internet